Pocket massage for stress relief - Maxwell-Hudson, Clare (Dorling Kindersley, 1996)
A soothing massage with scented essential oils is the perfect antidote to stress. It relaxes the muscles, boosts energy, has a beneficial effect on mood, and helps engender a feeling of well-being. This illustrated pocket book presents over 20 stress-relieving massage programmes carefully devised to restore zest for life at any time of day and in every situation. There are quick-fix self-massage treatments and sequences to do with a partner, profiles of restorative oils, and therapeutic blends to massage away headaches, ease aching muscles and promote peaceful sleep.